2020
DOI: 10.1093/ejcts/ezaa403
|View full text |Cite
|
Sign up to set email alerts
|

Is the EuroSCORE II reliable in surgical mitral valve repair? A single-centre validation study

Abstract: OBJECTIVES The EuroSCORE II is widely used to predict 30-day mortality in patients undergoing open and transcatheter cardiac surgery. The aim of this study is to evaluate the discriminatory ability of the EuroSCORE II in predicting 30-day mortality in a large cohort of patients undergoing surgical mitral valve repair in a high-volume centre. METHODS A retrospective review of our institutional database was carried on to find a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…That could be due to reduced heart function as a result of the disease, and the acute side effects of CPB and cardioplegia which may cause an impairment in heart function in the first few hours after surgery, thus increasing the probability of developing low-cardiac output syndrome and the respective impact. Similar to Carino et al (13), our study showed that a high EuroSCORE II was associated with an increased 30-day mortality and higher adverse long-term outcomes. EuroSCORE II is widely considered an important predictor for 30-day mortality after cardiac surgery.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…That could be due to reduced heart function as a result of the disease, and the acute side effects of CPB and cardioplegia which may cause an impairment in heart function in the first few hours after surgery, thus increasing the probability of developing low-cardiac output syndrome and the respective impact. Similar to Carino et al (13), our study showed that a high EuroSCORE II was associated with an increased 30-day mortality and higher adverse long-term outcomes. EuroSCORE II is widely considered an important predictor for 30-day mortality after cardiac surgery.…”
Section: Discussionsupporting
confidence: 90%
“…EuroSCORE II is widely considered an important predictor for 30-day mortality after cardiac surgery. It was validated in some studies in patients undergoing MV surgery (13,21,22) but we only found one study that explored the ability of EuroSCORE II to predict the 30-day mortality in patients undergoing MV surgery. They found that EuroSCORE II overestimates 30-day mortality (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, this is to the best of our knowledge the largest and first study to evaluate intraoperative hemoadsorption in a high-risk cohort undergoing cardiac surgery for infective endocarditis thus far. Regarding high-risk definition, the cutoff point for determining high-risk patients was set at a EuroSCORE II greater than 8% as the EuroSCORE II overestimates the operative mortality in cardiac surgical patients [ 30 , 31 ]. In order to compensate for this overestimation, we defined a high-risk patients as higher than 6% as in other studies.…”
Section: Discussionmentioning
confidence: 99%